A study on customers’ perception towards service quality of main counter at SSM Melaka / Noormaslifah Zainuddin - Zainuddin, Noormaslifah (Faculty of Business and Management, 2009)
This research presents a study, which was sought to take steps towards increasing both knowledge of how customers’ perceived the service quality delivered by the main counter of SSM and at the same time examines the distribution towards the service quality of main counter at SSM Melaka. Main counter is a place where people come and do many and different types of transactions. It is noteworthy to investigate how customers perceive the service quality of the main counter in order to deliver quality services to the customers throughout Malaysia. A survey was conducted through distribution of questionnaires to the customers. Hundred useable questionnaires were analyzed by using SPSS program based on the perception adopted from SERVQUAL model. The result indicates that most of customers who came to main counter of SSM Melaka very satisfied with the quality of service that delivered to them. From the second objective, it shows that the dimension of assurance received the highest perception score from customers in their rating score and dimension of tangible has received the second highest. The result indicates that most of the customers are more concern about feeling secure, politeness services, knowledgeable staff, also confident and believable staff. They also concern about the facilities provided, equipment used and also appearance of the staff which must be comfortable, up to date and professional. But at the same time, the customers perceived that the responsiveness dimension also important in delivering services. The findings also identified that there was a similarity on customer perception towards the effectiveness of service quality delivered by main counter of SSM Melaka, based on their demographic profile.